Bridging the Competence Gap: Pedagogical Adaptations of Elementary Teachers in Indonesian Inclusive Classrooms - Herlina Febriyani; Suyatno Suyatno; Lukis Alam (Jurnal Pendidikan Progresif, 2026)
One of the key indicators of success in the inclusive education process is the response of teachers and its principles. This response is influenced by various factors, such as educational background, experience working with children with special needs, self-confidence in conducting educational activities, and the difficulty level of the children. Therefore, this study aimed to explore teachers' experiences in implementing inclusive practices and adapting pedagogical strategies when teaching children with special needs in elementary schools in a rural area of Indonesia, specifically in the Bengkalis Regency, Riau Province. This qualitative study employed a phenomenological approach, and data were collected through interviews with 10 elementary school teachers from different schools. Data were analyzed using thematic analysis to identify key themes emerging from teachers’ experiences. They had varying ages, educational backgrounds, and teaching experience. The results showed that teachers initially felt confused, tense, and worried about their ability to guide inclusive students. This condition was followed by pressure and diverse student attitudes, which increased stress, sadness, and a desire to give up. However, teachers felt challenged and realized that every child is special, unique, and entitled to receive appropriate educational services. Through reflective practice and collaboration with colleagues, teachers began to develop adaptive strategies, such as differentiated instruction, emotional regulation, and individualized learning support. This study emphasizes that inclusive education in rural areas requires not only emotional readiness but also systemic support for teachers in building confidence and competence to serve diverse learners. Keywords: children with special needs, experience of teachers, inclusive school, phenomenological.